Gestão por competência em bibliotecas universitárias: análise do sistema integrado de bibliotecas da Universidade Estadual da Paraíba (UEPB) - Serafim, Andreza Nadja Freitas (2017)
It aims to verify which management actions by competence exist in the Integrated System of Libraries of the State University of Paraíba (UEPB). The concept of competency management is based on the conceptual matrix established by Valentim (2002), which points out competence as the capacity to mobilize knowledge, skills and individual skills in different contexts. This way, one should not link competence to the position, but rather to the collaborator who tends to understand the demands of the context on it and know how to mobilize his repertoire to serve them in an appropriate way. In methodological terms, it is a research delimited by the qualitative and quantitative approaches, which according to its objectives adopts procedures backed by the documentary and descriptive typology. To reach the objectives was used as a tool for collecting quantitative data, a semi-structured online questionnaire. The quantitative data was tabulated using the Microsoft Office Excel 2007 spreadsheet. Simple percent statistics were used to generate the charts and tables for each subcategory, seeking to associate with others of the same category. While the qualitative data were analyzed by the content analysis method. The first specific objective was achieved through the analysis of the Manual of Positions, Functions and Powers of UEPB Administrative Technical Servants, comparing the competencies indicated in the document to the detriment of the competencies suggested by CBO and those pointed out in the literature. With regard to the skills of librarians to meet the second specific objective, it has been generally identified that the majority positively points out the skills they possess. This made it possible to identify only some existing skills gaps that should be improved for the best exercise of activities in the SIB / UEPB libraries. With regard to the factors that influence the performance of the skills of the librarians surveyed, a question that sought to reach the third specific objective was the need to promote more training activities and spaces for learning together, so that there is an exchange of experiences between librarians . Allowing a mutual learning capable of favoring the development of the skills of librarians working in the SIB / UEPB. The research proposes structured actions to map the competencies of the librarians of the SIB / UEPB and so that the practices of management by competence can be implemented. In addition to the practical contribution to the field of research, when addressing management by competency in university libraries, it is expected that the study may bring theoretical contributions to the area of management and learning. And also provide subsidies for future reflections, enabling changes and advances in the scope of management of university libraries.